Human emotion processing accuracy, negative biases, and fMRI activation are associated with childhood trauma - Reisch, Alexis A.; Bessette, Katie L.; Jenkins, Lisanne M.; Skerrett, Kristy A.; Gabriel, Laura B.; Kling, Leah R.; Stange, Jonathan P.; Ryan, Kelly A.; Schreiner, Mindy Westlund; Crowell, Sheila E.; Kaufman, Erin A.; Langenecker, Scott A. (Frontiers in Psychiatry, 2023)
Introduction Emerging literature suggests that childhood trauma may influence facial emotion perception (FEP), with the potential to negatively bias both emotion perception and reactions to emotion-related inputs. Negative emotion perception biases are associated with a range of psychiatric and behavioral problems, potentially due or as a result of difficult social interactions. Unfortunately, there is a poor understanding of whether observed negative biases are related to childhood trauma history, depression history, or processes common to (and potentially causative of) both experiences. Methods The present cross-sectional study examines the relation between FEP and neural activation during FEP with retrospectively reported childhood trauma in young adult participants with remitted major depressive disorder (rMDD, n = 41) and without psychiatric histories (healthy controls [HC], n = 34). Accuracy of emotion categorization and negative bias errors during FEP and brain activation were each measured during exposure to fearful, angry, happy, sad, and neutral faces. We examined participant behavioral and neural responses in relation to total reported severity of childhood abuse and neglect (assessed with the Childhood Trauma Questionnaire, CTQ). Results Results corrected for multiple comparisons indicate that higher trauma scores were associated with greater likelihood of miscategorizing happy faces as angry. Activation in the right middle frontal gyrus (MFG) positively correlated with trauma scores when participants viewed faces that they correctly categorized as angry, fearful, sad, and happy. Discussion Identifying the neural mechanisms by which childhood trauma and MDD may change facial emotion perception could inform targeted prevention efforts for MDD or related interpersonal difficulties.